PEMBERIAN INFORMASI KESEHATAN IBU DAN ANAK MELALUI APLIKASI SAYANGI IBUKU - Nursanti, Siti; Ayusafitri, Widia (Jurnal Publisitas, 2019)
The high maternal mortality rate and infant mortality rate encourage the Karawang regency government through the Karawang District Health Office to increase public information literacy related to maternal and child health. Along with advances in information and communication technology the Karawang District Health Office launched an android-based application called Sayangi Ibuku. The purpose of this study was to find out how the communication efforts of the Karawang District Health Office in order to provide maternal and child health information through the Sayangi Ibuku application, this research uses qualitative research methods with a case study approach. The results of this study are the Karawang District Health Office using leaflets, browsers and training village coordinator midwives to convey the existence of the Sayangi Ibuku application, the Sayangi Ibuku application contains knowledge about female reproduction, pregnancy preparation, healthy pregnancy and general health information related to mother and child.